A desdita de Cálcis: a primeira experiência monástica de Jerônimo - Cruz, Marcus (Romanitas - Revista de Estudos Grecolatinos, 2020)
The second half of the fourth century in the region of the Mediterranean Sea Basin was a time particularly marked by profound transformations and conflicts. Among the changes and confrontations, we highlight on the one hand the rise of the monastic movement within the Christian community and on the other the disputes between the Christian and pagan intelligentsia around the control of the Paideia. These questions will be discussed based on the monastic experience experienced by Jerome in the desert of Chalcis between 374 and 377.
Keywords: Late Antiquity; Paideia; Monasticism; Jerome